III All-Russian scientific and practical conference “Phygital movement: Innovations, technologies and digital transformation in physical education and sports work of universities” (Kaliningrad, Immanuel Kant Baltic Federal University, April 11–12, 2025) - Sterlikova, Veronika Y.; Eremina, Ekaterina A. (Физическое воспитание и студенческий спорт)
From April 11 to 12, 2025, the III All-Russian scientific and practical conference ‘Phygital movement: innovations, technologies and digital transformation in physical education and sports work of universities» was held in Kaliningrad at the Immanuel Kant Baltic Federal University. The conference contributed to the development of phygital movement in the field of higher education, the unification of the scientific community, universities, sports and IT organizations to exchange best practices in the field of digitalization of sports and education. Particular attention was paid to the introduction of innovative technologies in educational processes, development of student sports and the creation of new forms of sports activity.